The role of Islamic religious education teachers in preventing bullying against students at Ma'arif Junior High School Bandung City - Nugraha, Yudi; Mulyani, Sri Pitri; Nurfadilah, Risa Aulia; Azzahra, Adinda; Ulfah, Ulfah (ARKA INSTITUTE, 2025)
Bullying is still a common occurrence in educational settings. It can have a negative impact on students' mental health, and can affect students' academic performance. Factors causing bullying that occurs in the school environment are caused by family factors, school environment factors that are unfair to students, peer factors, social media factors that are used improperly. Bullying that occurs in schools is done individually or in groups, so that teachers can play a role in preventing bullying behavior in schools, therefore this research was conducted to find out the problems and factors that cause bullying cases in Ma'arif Junior High School in Bandung. The purpose of the study was to determine the role of PAI teachers in preventing bullying, and to describe the forms of bullying and to find out the efforts made by PAI teachers in preventing bullying in schools. This study uses descriptive qualitative research methods through interviews, observation and documentation using Miles and Huberman data analysis, namely, data reduction, data presentation and conclusion drawing. The results showed that the pai teacher plays a role in preventing bullying by carrying out several roles at school including as a role model, as an initiator, as an evaluator and as a mentor in preventing bullying that occurs at Ma'arif Junior High School in Bandung City, among which the forms of bullying that occur at Ma'arif Junior High School in Bandung City are verbal, physical, relational bullying. The efforts made by PAI teachers in preventing bullying in schools by running several school programmes, namely the istighosah programme, habituation of dhuha prayer, kitab akhlaq lil banin, kitab ta'lim muta'lim and flag ceremonies.